2022
DOI: 10.1186/s12936-022-04225-3
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perceptions on the deployment of multiple first-line therapies for uncomplicated malaria: a qualitative study in the health district of Kaya, Burkina Faso

Abstract: Background In Burkina Faso, malaria remains the first cause of medical consultation and hospitalization in health centres. First-line case management of malaria in the country’s health facilities is based on the use of artemisinin-based combination therapy (ACT). To optimize the use of these anti-malarial drugs in the perspective of mitigating the emergence of artemisinin resistance, which is a serious threat to malaria control and elimination, a pilot programme using multiple first-line therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…ACT registrations for first-line treatment reflect the status at the time of the study for each country. Countries conducting MFT pilots at the time of the study (Kenya and Burkina Faso) were excluded because stakeholders' perceptions and attitudes towards MFT had already been investigated and published [18,20]. The perceptions of MFT in countries that did not have practical experience with the intervention were prioritized, to identify potential barriers and drivers of implementation in advance.…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…ACT registrations for first-line treatment reflect the status at the time of the study for each country. Countries conducting MFT pilots at the time of the study (Kenya and Burkina Faso) were excluded because stakeholders' perceptions and attitudes towards MFT had already been investigated and published [18,20]. The perceptions of MFT in countries that did not have practical experience with the intervention were prioritized, to identify potential barriers and drivers of implementation in advance.…”
Section: Study Settingmentioning
confidence: 99%
“…Feasibility and acceptability studies can help identify potential barriers and facilitators of implementation. A recent pilot conducted in Burkina Faso investigated stakeholders' perceptions of an MFT intervention that relied on a segmentation approach [18]. Authors found that the adherence by both the population and key stakeholders would depend on treatment efficacy, low severity level of side effects, cost, and drug availability.…”
Section: Introductionmentioning
confidence: 99%
“…Interruptions in the supply chain, inconsistent stocking, and inadequate funding persist in Angola's drug procurement but it is not clear that these result from the choice to deploy multiple therapies at once ( 65 ). Burkina Faso adopted AL and ASAQ simultaneously in 2005 ( 66 ), and recent field trials and interviews have indicated a general level of acceptance of MFT as a worthwhile national drug policy ( 67 69 ). The major challenge in Burkina Faso was patient and provider preference for AL, which led to AL being used as treatment of choice for about 70% of uncomplicated falciparum cases by 2018 ( 70 ).…”
Section: Mft In Practicementioning
confidence: 99%
“…Recent studies suggest that perceptions of MFT are changing and moving towards acceptance ( 67 , 69 ). The simplest starting point for communication around MFT is one that establishes the equivalence of certain antimalarial therapies ( 67 , 71 )—for example that AL, ASAQ, and AS-pyronaridine have equal efficacies and equal resistance risks—as this will help steer the health system to a uniform drug distribution in which each of these ACTs is prescribed or sold in approximately equal amounts. If the therapies are substantially different in efficacy or resistance risk, they should not be deployed together in a simple equal-distribution MFT policy.…”
Section: Mft In Practicementioning
confidence: 99%
“…Volatile terpenes can also serve as interspecific or interplant “alarm” signals to trigger the defense responses of neighboring plants [ 20 ]. Terpenes, such as artemisinin, are used to treat malaria [ 21 ].…”
Section: Introductionmentioning
confidence: 99%